On the Gravitational Force on Anti‐Matter. Issue 1 (10th October 2020) - Caldwell, Allen; Dvali, Gia
Abstract: A number of experiments are currently underway on antimatter, particularly anti‐hydrogen, to test whether the fundamental interactions behave the same way as for matter. Here we present a simple argument showing that a bound on a difference in gravitational forces exerted on matter and antimatter is already so severe that is goes well beyond the sensitivity of the above measurements. Abstract : A number of experiments are currently underway on antimatter, particularly anti‐hydrogen, to test whether the fundamental interactions behave the same way as for matter. Here a simple argument is presented showing that a bound on a difference in gravitational forces exerted on matter and antimatter is already so severe that is goes well beyond the sensitivity of the above measurements.